Dividing the spoils : pensions, privatization, and reform in Russia's transition - Kapstein, Ethan B., 1953- 1953- (Policy research working paper, 2000)
The gains from the transition in post-communist Russia were captured by the new managerial class, which won rents from the state in the form of privatized enterprises, state subsidies, credits, and opportunities for tax evasion. Those rents reduced state revenues that could have supported social policy - including pension reform, which in turn could have fueled industrial restructuring. With neither pension reform nor industrial restructuring, Russia's economy has continued to shrink. Kapstein and Milanovic present a political economy model in which policy is the outcome of an interaction between three actors: government (G), managers and workers (W), and transfer recipients (P). The government's objective is to stay in power, for which it needs the support of either P or W. It can choose slow privatization with little asset stripping and significant taxation, thus protecting the fiscal base out of which it pays pensioners relatively well (as in Poland). Or it can give away assets and tax exemptions to managers and workers, who then bankroll it and deliver the vote, but it thereby loses taxes and pays little to pensioners (as in Russia).The authors apply this model to Russia for the period 1992-96. An empirical analysis of electoral behavior in the 1996 presidential election shows that the likelihood of someone voting for Yeltsin did not depend on that person's socioeconomic group per se. Those who tended to vote for Yeltsin were richer, younger, and better educated and had more favorable expectations of the future. Entrepreneurs, who had more of these characteristics, tended to vote for Yeltsin as a result, while pensioners, who had almost none, tended to vote against Yeltsin.